Modulation of porcine intestinal epitheliocytes immunetranscriptome response by Lactobacillus jensenii TL2937 - Kobayashi, Hisakazu (2016)
In order to evaluate probiotic strains applicable for the beneficial immunomodulation of the porcine gut (immunobiotics), we previously developed a porcine intestinal epitheliocyte cell line (PIE cells). Here, transcriptomic studies using PIE cells were performed considering that this information would be valuable for understanding the mechanisms involved in the protective activity of the immunobiotic strain Lactobacillus jensenii TL2937 against intestinal inflammatory damage in pigs. In addition, those studies would provide criteria for selecting biomarkers for the screening of new immunobiotic strains. We performed microarray analysis to investigate the transcriptomic response of PIE cells to the challenge with heat-stable Enterotoxigenic Escherichia coli (ETEC) pathogen-associated molecular patterns (PAMPs) and, the changes induced by L. jensenii TL2937 in that response. The approach allowed us to obtain a global overview of the immune genes involved in the response of PIE cells to heat-stable ETEC PAMPs. We observed that L. jensenii TL2937 differently modulated gene expression in ETEC PAMPs-challenged PIE cells. Microarray and RT-PCR analysis indicated that the most remarkable changes in PIE cells transcriptomic profile after heat-stable ETEC PAMPs challenge were observed in chemokines, adhesion molecules, complement and coagulation cascades factors. In addition, an anti-inflammatory effect triggered by TL2937 strain in PIE cells was clearly demonstrated. The decrease in the expression of chemokines (CCL8, CXCL5, CXCL9, CXCL10, and CXCL11), complement (C1R, C1S, C3, and CFB), and coagulation factors (F3) by L. jensenii TL2937 supports our previous reports on the immunoregulatory effect of this strain. These results provided clues for the better understanding of the mechanism underlying host-immunobiotic interaction in the porcine host. The comprehensive transcriptomic profiles of PIE cells provided by our analyses successfully identified a group of genes, which could be used as prospective biomarkers for the screening and evaluation of new anti-inflammatory immunobiotics for the prevention of inflammatory intestinal disorders in pigs.